2018
DOI: 10.1113/jp275999
|View full text |Cite
|
Sign up to set email alerts
|

mGluR5‐dependent modulation of dendritic excitability in CA1 pyramidal neurons mediated by enhancement of persistent Na+ currents

Abstract: Dendritic Na channels in pyramidal neurons are known to amplify synaptic signals, thereby facilitating action potential (AP) generation. However, the mechanisms that modulate dendritic Na channels have remained largely uncharacterized. Here, we report a new form of short-term plasticity in which proximal excitatory synaptic inputs to hippocampal CA1 pyramidal neurons transiently elevate dendritic excitability. High-frequency stimulations (HFS) to the Schaffer collateral (SC) pathway activate mGluR5-dependent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
5
20
0
Order By: Relevance
“…We recently reported that high-frequency stimulations (HFS; 100 Hz for 0.5 s) to Schaffer Collateral (SC) synapses trigger mGluR-dependent Ca 2+ release in apical dendrites of CA1-PN, which in turn induce calmodulin-dependent increase in persistent Na current (I Na,P ) that leads to E-S potentiation [ 32 ]. To investigate the effects of dendritic I Na,P increases on intrinsic excitability of CA1-PNs, we tested whether action potential (AP) firing in CA1-PNs evoked by depolarizing current injection is affected by HFS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that high-frequency stimulations (HFS; 100 Hz for 0.5 s) to Schaffer Collateral (SC) synapses trigger mGluR-dependent Ca 2+ release in apical dendrites of CA1-PN, which in turn induce calmodulin-dependent increase in persistent Na current (I Na,P ) that leads to E-S potentiation [ 32 ]. To investigate the effects of dendritic I Na,P increases on intrinsic excitability of CA1-PNs, we tested whether action potential (AP) firing in CA1-PNs evoked by depolarizing current injection is affected by HFS.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the group I mGluRs are coupled to G q protein-mediated Ca 2+ signaling pathways, which ultimately modulate various ion channels that shape the input-output relationship of neuronal network. We have recently demonstrate that high-frequency stimulation (HFS) of the Schaffer collateral pathway leads to the reliable activation of postsynaptic mGluR5 in CA1-PNs, producing the short-term potentiation of EPSP-to-spike (E-S) coupling [ 32 ]. We showed the involvement of persistent Na + currents (I Na,P ) in proximal apical dendrites in mGluR5-dependent E-S potentiation, but the role of dendritic I Na,P enhancement in intrinsic excitability and firing properties in CA1-PNs remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the increase in excitability could reflect activity-dependent changes in excitability that are not directly related to learning or retention processes. For example, repetitive activation of excitatory inputs to hippocampal pyramidal cells has been shown to increase persistent sodium currents in the post-synaptic dendrites [ 47 ]. The changes are caused by activation of metabotropic glutamate receptor-mediated calcium signalling and lead to enhanced dendritic excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Data are mean ± SEM; 2-way ANOVA, *P < 0.05, **P < 0.01; ns, not significant. The resolution for 2PE of alloswitch achieved under these experimental conditions was obtained by fitting to a Gaussian function (FWHM; 6.2 ± 2. onto the apical dendritic arbor, but not the somatic region, of CA1 neurons can induce persistent sodium conductance (43). However, further spatially resolved insight was not possible, because puffing of the agonist evokes an extended recruitment of receptors while it travels away from the ejection site.…”
Section: Efficacy Of 2pe Of Alloswitch Is 30% Of 1pe To Rescue Silencmentioning
confidence: 99%